Roman Rybarski wobec działań politycznych obozu sanacyjnego w latach 1930–1939 w świetle wystąpień sejmowych i publicystyki - Zychowicz, Damian (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
Roman Rybarski was one of the leading representatives of the National Party in the Second Polish Republic. As a supporter of parliamentary democracy and a political opponent of the Piłsudskiites, he was critical of the actions of the Sanation camp. Rybarski expressed his criticism in the press and at the parliamentary from the floor of the Sejm. The aim of this article is to present this criticism in the period from the Brest events (1930) to 1939, and to assess whether Roman Rybarski’s concerns about the totalitarianisation of Poland were justified. The work will be based on parliamentary transcripts of Rybarski’s speeches and his journalism.
Keywords: Rybarski, Roman (1887-1942); sanacja; polityka władz sanacyjnych; II Rzeczpospolita; Stronnictwo Narodowe; narodowcy; autorytaryzm; totalitaryzm